What matters for life satisfaction among the oldest-old? Evidence from China - Ng, S.T.; Tey, N.P.; Asadullah, M.N. (Public Library of Science, 2017)
Objective The world population is aging rapidly and the well-being of older people is of great interest. Therefore, this study investigates the determinants of life satisfaction among the oldest-old (i.e. individuals aged 80 or over) in China. Materials and methods We use the 2011/2012 Chinese Longitudinal Healthy Longevity Survey data (n = 6530) for this paper. Logistic regression is used to analyse the effects of socio-demographic, economic, health, instrumental activities of daily living, family and community factors on life satisfaction and depression among the oldest-old in China. Results Our analysis confirms the significance of many factors affecting life satisfaction among the oldest-old in China. Factors that are correlated with life satisfaction include respondent's sex, education, place of residence, self-rated health status, cognitive ability (using mini mental state examination), regular physical examination, perceived relative economic status, access to social security provisions, commercialized insurances, living arrangements, and number of social services available in the community (p<0.05 for all these variables). Although life satisfaction is negatively associated with instrumental activities of daily living (β =-0.068, 95%CI =-.093:.043), and depression (β =-0.463, 95%CI =-.644:.282), the overall effect of self-rated health status is positive (p<0.001). This confirms the primacy of health as the determinant of well-being among the oldest-old. Conclusions Majority of the oldest-old in China rated their life satisfaction as good or very good. Our findings show that health and economic status are by far the most significant predictors of life satisfaction. Our finding on the primacy of health and relative income as determinants of well-being among the oldest-old, and the greater influence of self-rated health status over objective health measures is consistent with the findings of many past studies. Our results suggest that efforts should be directed at enhancing family support as well as health and social service provisions in the community to improve life satisfaction of older people.